Water environmental capacity analysis and eutrophication assessment of water-supplied reservoirs - Peng Chen; Guoping Ye; Xianqiang Xu; Weihan Xi; Dong Xu (Desalination and Water Treatment)
The protection of water quality in reservoirs, particularly those designated for water supply, has garnered increasing attention for environmental management purposes. In this paper, the Shuangxikou Reservoir in Yuyao was chosen as a case study. The pollutant load at various points within the reservoir was analyzed and its eutrophication level was evaluated through a combination of site surveys and regular monitoring. Additionally, a model trial algorithm was utilized to investigate the water environment capacity concerning key pollutant indicators such as COD, NH3-N, TN, and TP in Shuangxikou Reservoir. The results indicated that the nutrient level in Shuangxikou Reservoir fell within the mid-trophic range, with water quality being superior in the central region compared to other areas. However, when compared to the water quality target of Class II surface water mandated by water environment functional zoning, the current TN and TP content in the reservoir exceeds acceptable levels. Consequently, targeted measures are imperative to enhance water quality in the reservoir.